“That Could Be Me Squishing Chips on Someone’s Car.” How Friends Can Positively Influence Bullying Behaviors - Burns, Sharyn; Cross, D.; Maycock, Bruce (Springer, 2010)
Semi-structured one-on-one interviews with a purposive sample of 51 grade 7 students (12 years old) who reported bullying others explored what might encourage students to stop bullying others. The theoretical perspectives of symbolic interactionism, in particular the development of self and definition of the situation, were used to inform this study. Dissonance theory was used to understand how students felt about their bullying behaviors. The theme of peer group emerged as an influence when considering desisting bullying others. Feelings of dissonance reinforced by peers and the need to be accepted by peers facilitated positive changes if significant peers disapproved of bullying. Some students changed friendship groups to move away from negative situations, representing significant development of self. School-based programs can work to enhance the positive influence of prosocial students, to focus on the development of self, and to reduce the social status achieved by some through bullying others.